1995
DOI: 10.1073/pnas.92.16.7148
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of a mannitol dehydrogenase cDNA from plants reveals a function for the pathogenesis-related protein ELI3.

Abstract: Mannitol is the most abundant sugar alcohol in nature, occurring in bacteria, fungi, lichens, and many species of vascular plants. Celery (Apium graveolens L.), a plant that forms mannitol photosynthetically, has high photosynthetic rates thought to result from intrinsic differences in the biosynthesis of hexitols vs. sugars. Celery also exhibits high salt tolerance due to the function of mannitol as an osmoprotectant. A mannitol catabolic enzyme that oxidizes mannitol to mannose (mannitol dehydrogenase, MTD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 20 publications
(46 reference statements)
3
75
0
Order By: Relevance
“…The AtCAD-B paralogs corresponding to ELI-3 proteins have been studied previously and were originally identified as part of the defense response in parsley (Petroselinum crispum) and in Arabidopsis (Kiedrowski et al, 1992). Williamson et al (1995) and Somssich et al (1996) demonstrated that ELI-3 was neither a CAD nor a malate dehydrogenase but rather a benzyl alcohol dehydrogenase, which accepts various benzaldehyde substrates. In our phylogenetic analysis, these proteins (AtCAD-A, AtCAD-B1, and -B2) fall within the same cluster as PtSAD, which has been recently identified and characterized in poplar (Li et al, 2001).…”
Section: Atcad-c and Atcad-d Belong To A Small Multigene Family In Armentioning
confidence: 99%
“…The AtCAD-B paralogs corresponding to ELI-3 proteins have been studied previously and were originally identified as part of the defense response in parsley (Petroselinum crispum) and in Arabidopsis (Kiedrowski et al, 1992). Williamson et al (1995) and Somssich et al (1996) demonstrated that ELI-3 was neither a CAD nor a malate dehydrogenase but rather a benzyl alcohol dehydrogenase, which accepts various benzaldehyde substrates. In our phylogenetic analysis, these proteins (AtCAD-A, AtCAD-B1, and -B2) fall within the same cluster as PtSAD, which has been recently identified and characterized in poplar (Li et al, 2001).…”
Section: Atcad-c and Atcad-d Belong To A Small Multigene Family In Armentioning
confidence: 99%
“…Although CtCAD1 may not be dominant in monolignol biosynthesis, it may have other roles in plant metabolism, such as in stress-induced defenses, similar to the ELI3 genes encoding pathogen defense-related CADs in Apium graveolens, Arabidopsis, or P. crispum (parsley) (Logemann et al 1997;Somssich et al 1996;Williamson et al 1995). It is also possible that CtCAD1 is involved in extremely localized processes, such as lignification during Arabidopsis silique or anther dehiscence (Liljegren et al 2000;Mitsuda et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A phylogenetic tree (Figure 2) constructed using the neighbor-joining method showed that CtCAD1 and CtCAD3 were located in a clade that included P. tremuloides sinapaldehyde-specific SAD (PtreSAD) and plant defense-related CADs from A. thaliana (Somssich et al 1996), Apium graveolens (Williamson et al 1995), Camptotheca acuminata (Valletta et al 2010), Ocimum basilicum (Iijima et al 2006), Petrosilinum crispum (Kiedrowski et al 1992), and the lignin-related CAD from Fragaria×ananassa cv. Chandler (Blanco-Portales et al 2002).…”
Section: Ctcad Phylogenetic Analysismentioning
confidence: 99%
“…Such studies should provide insight into the roles of polyols in primary carbon metabolism. Given the increasing number of studies linking sugar alcohols to stress tolerance (Ahmad et al, 1979;Hirai, 1983;Ranney et al, 1991;Tarczynski et al, 1993;Everard et al, 1994;Stoop and Pharr, 1994;Pharr et al, 1995;Thomas et al, 1995;Tattini et al, 1996), we should also gain further insight into the mechanisms involved in the regulation of sugar alcohol levels in plants subjected to abiotic stress.…”
Section: Discussionmentioning
confidence: 99%
“…It is a mannito1 producer and approximately 50% of newly assimilated carbon is partitioned into this compound in mature leaves. Both the anabolic (Rumpho et al, 1983;Loescher et al, 1992) and catabolic (Pharr et al, 1995) pathways have been described. The synthetic pathway appears to be present in other mannitol-synthesizing higher plant species Harloff and Wegmann, 1993;Simier et al, 1994) and comprises three unique enzymatic steps: (a) isomerization of Fru-6-P to Man-6-P by Man-6-P isomerase; (b) reduction of Man-6-P to mannitol-1-phosphate by M6PR; and (c) dephosphorylation of mannitol-1-phosphate to mannitol by mannitol-1-phosphate phosphatase.…”
mentioning
confidence: 99%